ความคิดทางการเมืองในสามก๊กและเจ้าผู้ปกครอง - ไพรัตน์ เทศพานิช (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The objective of this thesis is to study political thoughts in the Three Kingdoms and Machiavelli s the Prince. It focuses on the concept of "machiavellian". This thesis. used the close textual analysis, to study some important and major aspects of "machiavellian" in both the Three Kingdoms and the Prince.The result of the study shows that : 1. regarding machiavellian , there exist similarities between - the Prince and the Three Kingdoms ; 2. regarding the art of writing, the Three Kingdoms can be deemed more machiavellian than the Prince.